2012
DOI: 10.1007/s00339-012-6921-7
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous wrinkling pattern of a constrained thin film membrane

Abstract: The wrinkling morphology of an inhomogeneously constrained thin film membrane is explored using finite element simulations, where a small circular area in a thin sheet undergoes expansion, and buckles emerge due to differential in-plane deformation. The local wrinkling patterns are characterized by the normalized circular (inner) area size, the modulus mismatch between the inner and outer regions, and the normalized stress in the inner area. As the stress increases, the morphology transits from ripplelike to p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 28 publications
(36 reference statements)
0
3
0
Order By: Relevance
“…predicted a similar effect, i.e. an increase in the number of wrinkles when the Young’s modulus of the surrounding film becomes increasingly larger compared to that of the central membrane 42 . Moreover, laser interferometry experiments demonstrate the emergence of first generation wrinkles, which are the wrinkles appearing at the rim, by clearly showing out-of-plane deformations.…”
Section: Resultsmentioning
confidence: 81%
“…predicted a similar effect, i.e. an increase in the number of wrinkles when the Young’s modulus of the surrounding film becomes increasingly larger compared to that of the central membrane 42 . Moreover, laser interferometry experiments demonstrate the emergence of first generation wrinkles, which are the wrinkles appearing at the rim, by clearly showing out-of-plane deformations.…”
Section: Resultsmentioning
confidence: 81%
“…In recent studies by other groups, the wrinkling pattern of a small circular area in a large elastic sheet were theoretically and experimentally investigated and patterns similar to Figure 12(b) were observed. 33,34 In contrast, because we utilized the edges of elastic sheets in order to control the wrinkling pattern, the control mechanism was different from that of those studies.…”
Section: Serrated Structures Obtained Using Small Samplesmentioning
confidence: 97%
“…The buckling phenomenon of thin films from substrate has been a hot topic in recent years [1][2][3][4][5][6][7][8] and the mechanism of the buckling behavior has been studied broadly. Previous research work has reported the buckling induced either by thermal deformation mismatch or compressive stress [9].…”
Section: Introductionmentioning
confidence: 99%